Molecular Detection of Newcastle Disease Virus from Field Outbreaks in Assam, India - Deka, Pubaleem; Nath, Mrinal K.; Das, Sangeeta; Deka, Pankaj; Hazarika, Ritam; Das, Gunajit; Sarma, Mihir (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was carried out to detect the Newcastle disease virus (NDV) from various field outbreaks in Assam. Nine hundred ninety-twoclinical and post -mortem samples during 2018-2021 were collected from the backyard and commercial poultry farms and subjectedto molecular diagnosis of NDV by Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR). NDV could be detected in 58.78% tissuesamples and 22.55% cloacal swabs collected from suspected poultry cases by RT-PCR. Organ wise study suggests that highest NDV(92.94%) was detected in trachea followed by spleen (90.62%), lung (86.95%), caecal tonsils (77.08%), proventriculus (60.81%), brain(48.91%), intestines (31.50%) and kidney (23.07%). Hence, the collection of specific tissue samples from field outbreaks for the detection of NDV is of paramount importance. In addition, RT-PCR can be considered a highly sensitive detection method for rapid and confirmative diagnosis of Newcastle disease virus.
Keywords: : Newcastle disease virus; Poultry; primers; RT-PCR